Abundance of coral-polyp-eating gastropods Drupella cornus in Bunaken National Park, Indonesia: indicating anthropogenic impact? - Boneka, Farnis B; Mamangkey, N Gustaf F (AQUATIC SCIENCE & MANAGEMENT, 2013)
Corallivorous gastropods, Drupella cornus are living in the Indo Pacific coral reefs. To assess the distribution of the snails at Bunaken National Park in Indonesia, a study has been conducted on three zones established in three main islands of the park: core, tourism, and exploitation zones. The zones represent degrees of human interventions in which the least intervention is for core zone, moderate for tourism zone and high for the exploitation zone. The results showed that degrees of human interventions are related to the density of snails where the least human intervention zone (the core zone) had low numbers of snails while the high human intervention (exploitation) zone had high numbers of snails. Three corals in the zones that were preferred by the snails were: Montipora spp., Acropora spp., and Porites spp. The numbers of snails living on the corals followed the percent of coral cover© Gastropod pemakan polip karang, Drupella cornus hidup di areal terumbu karang Indo-Pasifik. Untuk mengetahui distribusi dari siput di Taman Nasional Bunaken, sebuah studi telah dilakukan pada tiga zona yang ditetapkan di tiga pulau utama di taman nasional ini: zona inti, zona pariwisata, dan zona pemanfaatan. Hasil penelitian ini menunjukkan bahwa tinggi-rendahnya intervensi manusia berhubungan dengan kepadatan siput di mana zona yang memiliki intervensi terendah (zona inti) memiliki jumlah siput sedikit sementara zona dengan intervensi tertinggi (zone pemanfaatan) memiliki jumlah siput terbanyak. Tiga spesies karang di ketiga zona ini yang disukai oleh siput adalah Montipora spp., Acropora spp., and Porites spp. Jumlah siput yang hidup di karang mengikuti jumlah persen tutupan karang©